A mm-wave T-R RF switch incorporated with CSRR switchable DGS for 5G application - Othman, A.; Majid, H.A.; Al-Fadhali, Najib; Shairi, Noor Azwan; Zobilah, A.M. (2023)
This paper proposes a millimeter-wave transmit/receive switch that applies a switchable defected ground structure for 5G applications. The switch shows a high isolation level of up to 42 dB and can be operated optimally around 24.23 to 28.31 GHz. Furthermore, the switch's accessibility to swap between bandstop and allpass responses gives it an edge in being appropriately used in 5G time division duplex communication.